Using ISSR genomic fingerprinting to study the genetic differentiation of Artemia leach, 1819 (Crustacea: Anostraca) from Iran and neighbor regions with the focus on the invasive American Artemia franciscana - Eimanifar, Amin; Asem, Alireza; Wang, Pei-Zheng; Li, Weidong; Wink, Michael (Diversity, 2020)
Due to the rapid developments in the aquaculture industry, Artemia franciscana, originally an American species, has been introduced to Eurasia, Africa and Australia. In the present study, we used a partial sequence of the mitochondrial DNA Cytochrome Oxidase subunit I (mt-DNA COI) gene and genomic fingerprinting by Inter-Simple Sequence Repeats (ISSRs) to determine the genetic variability and population structure of Artemia populations (indigenous and introduced) from 14 different geographical locations in Western Asia. Based on the haplotype spanning network, Artemia urmiana has exhibited higher genetic variation than native parthenogenetic populations. Although A. urmiana represented a completely private haplotype distribution, no apparent genetic structure was recognized among the native parthenogenetic and invasive A. franciscana populations. Our ISSR findings have documented that despite that invasive populations have lower variation than the source population in Great Salt Lake (Utah, USA), they have significantly revealed higher genetic variability compared to the native populations in Western Asia. According to the ISSR results, the native populations were not fully differentiated by the PCoA analysis, but the exotic A. franciscana populations were geographically divided into four genetic groups. We believe that during the colonization, invasive populations have experienced substantial genetic divergences, under new ecological conditions in the non-indigenous regions.
Gesehen am 23.06.2020